Does the stick make the carrot more attractive? State mandates and uptake of renewable heating technologies - Martin Achtnicht; Robert Germeshausen; Kathrine von Graevenitz (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2017)
In this paper, we investigate the effect of the state-level renewable heating mandate for existing homes in Baden-Wuerttemberg, Germany's third largest federal state. The mandate requires homeowners to supply at least 10 % of their heat demand with renewable energy when they replace their existing heating system. To assess the impact of the renewable heating standard on the uptake of renewable heating systems, we use unique data on a federal government subsidy scheme and exploit geographic differences in state laws over time. We find no evidence of an effect of the mandate even after restricting distance to the state border and refining the data set through matching on population and building characteristics. These findings are unchanged, when we allow effects to vary across space or over time. While energy efficiency and renewable standards are often criticized for not being cost-effective, our results challenge the widespread view that a standard is nevertheless successful in achieving its policy goal.
Keywords: Q4; Q48; O33; Q58; H23; 330; Technology diffusion; Building regulations; Subsidies; Renewable energy sources